“Ecrif framework applied for teaching speaking skills in English from pre-service teachers’ and students’ perspectives.” - Nieto Toapanta, Conie Masiel (2023)
Developing speech skills in students can be a drawback when a good methodology and structure is not correctly applied. That is why ECRIF is constituted as a framework with a five-stage structure, each of which should be adapted to the level and needs of the students. However, trainee teachers have different perspectives on the ECRIF framework. For this reason, the present research project aimed to identify the perspectives and experiences of trainee teachers regarding the use of the ECRIF method for the development of English language speaking skills at the Technical University of Cotopaxi. This is a qualitative study in which convenience sampling was used. A semi-structured open-ended interview was used with 5 seventh semester students. The results showed different categories of perspectives and experiences in which the following themes stood out: ECRIF conceptualization, speaking skills growth, and students' interaction time, ECRIF Lesson planning difficulty, assistance of the ECRIF framework in EFL classes, Teacher's interaction time, students' difficulty levels in communication, Pre-service teacher motivation over students, ECRIF framework application personal experience, and speaking skills application with ECRIF framework success. These issues raised showed the reality that the trainee teachers were going through and they emphasized that at the beginning it was a difficult task to plan and develop each lesson, as their framework is normally used in teaching English at the higher level. Also, time was one of their biggest adversaries as it requires a lot of time and in the real situation in which the trainees and the teacher trainees are working, it was complicated to comply with it. It is concluded that the ECRIF framework allows students to improve oral skills with the help of teachers and with the use of interactive activities to maintain verbal communication. In addition, the development of an objective that meets the needs of each student should be taken into account in lesson planning. However, limited time makes it difficult to apply the framework in a single class since ECRIF is more suitable for intermediate to advanced English learners and according to what was obtained the students only had basic levels.